2020
DOI: 10.1002/smll.202001647
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic Agents: Nanocarriers in Controlled Release

Abstract: Thrombosis is a life-threatening pathological condition in which blood clots form in blood vessels, obstructing or interfering with blood flow. Thrombolytic agents (TAs) are enzymes that can catalyze the conversion of plasminogen to plasmin to dissolve blood clots. The plasmin formed by TAs breaks down fibrin clots into soluble fibrin that finally dissolves thrombi. Several TAs have been developed to treat various thromboembolic diseases, such as pulmonary embolisms, acute myocardial infarction, deep vein thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 137 publications
0
40
0
Order By: Relevance
“…Therefore, Huang et al reported an activated-platelet-sensitive nanocarrier capable of inducing selective thrombolysis through targeted delivery and controlled release of tPA to blood clot (Huang et al, 2019). The nanothrombolytic system loaded with tPA was based on FIGURE 2 | Illustration of the principles of thrombolysis in a fibrin surface and circulating blood environment (Hassanpour et al, 2020). This figure describes the catalytic principle of the conversion of plasminogen to plasmin according to the binding method of the plasminogen activator [e.g., tissue-type plasminogen activator (tPA), urokinase (UK), and streptokinase (SK)]) Plasminogen specifically binds to the surface of the fibrin blood clot.…”
Section: Targeted Chemical Modification Of Nanocarriers and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Huang et al reported an activated-platelet-sensitive nanocarrier capable of inducing selective thrombolysis through targeted delivery and controlled release of tPA to blood clot (Huang et al, 2019). The nanothrombolytic system loaded with tPA was based on FIGURE 2 | Illustration of the principles of thrombolysis in a fibrin surface and circulating blood environment (Hassanpour et al, 2020). This figure describes the catalytic principle of the conversion of plasminogen to plasmin according to the binding method of the plasminogen activator [e.g., tissue-type plasminogen activator (tPA), urokinase (UK), and streptokinase (SK)]) Plasminogen specifically binds to the surface of the fibrin blood clot.…”
Section: Targeted Chemical Modification Of Nanocarriers and Applicationsmentioning
confidence: 99%
“…Taking into account the cost of surgical treatment and the damage it causes to the body, the application of thrombolytic drugs has increasingly become an important strategy. Thrombolytic agents include tissue plasminogen activators (tPA), recombinant tissue plasminogen activators (rtPA), urokinase (UK), streptokinase (SK), and other plasminogen activators (PAs; Marder, 2013 ; Cheng et al, 2018 ; Zamanlu et al, 2018 ; Ma et al, 2019 ; Hassanpour et al, 2020 ). The diverse antigenicity, half-life, lytic potential, fibrin specificity, and hemorrhagic risks associated with these agents lead to their differing effectiveness ( Marshall, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, nanotechnology approaches have demonstrated a promising possibility to improve the pharmacokinetics and biodistribution profile of many drugs. [21,23,24] Some studies have shown that the pH gradients between ischemic and normal tissues are used to achieve targeted release. [25] However, the instability of the local environment and the physiological state of other parts of the body limits the release of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the list of examples mentioned above is only partial; for a more detailed introduction of thrombolytic agents and nanocarrier approaches for thrombolytics, readers are directed to recent, comprehensive reviews by Hassanpour and coworkers 17 and Zenych and coworkers. 18 There certainly is a growing and/or renewed interest in this area.…”
mentioning
confidence: 99%